PERANCANGAN SISTEM INFORMASI PERHITUNGAN INSENTIF (BONUS) SALES CONSULTAN/COUNTER PADA PT. LAUTAN BERLIAN UTAMA MOTOR PADA MITSUBISHI MOTOR - Dian Gustina; Samsiah Samsiah (Fakultas Ilmu Komputer dan Desain - Unsurya, 2019)
In the current era of globalization, information technology is very important to support the smooth activities of an organization which is a means of information and communication that is useful in the right and accurate decision making process. At present there are still many companies that use manual systems in calculating sales bonuses / counter incentives and recording their administration manually, such as employee data, employee sales data, and employee bonus data. One company that still adheres to this system is PT. Lautan Berlian Utama Motor. To minimize the occurrence of errors in the calculation process of sales incentives consultants / counters the author conducted research to design an information system for calculating incentive (bonus) sales consultants / counters at PT. Lautan Berlian Utama Motor. Data collection method is done by observation, interview, literature study. With this sales incentive calculation information system design application, it is expected to accelerate the operational activities process with interested parties in the sales incentive calculation process can run well.Â Keyword : System, Information, car sales, incentive, incentive report, My Sql.